Combination of regional characteristics for start-up activity in Switzerland - Franz Kronthaler; Katharina Becker; Kerstin Wagner (European Regional Science Association (ERSA), 2012)
Start-up activities are considered to be important for regional economic development which varies considerably between regions. As new firm formation and growth is strongly influenced by regional conditions, we analyse the role of regional conditions and their impact on start-up activities. In particular, this study assumes that the combination of the determinants, which are considered to have an impact on firm formations rates, influences regional start-up activity. To test this assumption the paper uses a two-step procedure, employing cluster analysis combined with non-parametric testing. Firstly, homogenous types of regions with regard to their structural characteristics conducive for entrepreneurial activities are formed with the help of cluster analysis. Secondly, Kruskal-Wallis test and Mann-Whitney test are used to find out whether the different types of regions with a specific composition of factors perform equally in new firm formation. The analysis is based on the spatial level of Swiss `mobilité spatiale' regions (MS-regions). MS-regions are functional units based on economic interaction and commuting movements. The research strategy makes it possible to discuss whether different regional combinations of factors lead to high or low similar start-up rates within regions. The results show firstly that regions with an overall high potential, due to their factor endowment, have in fact high start-up rates, whereas regions with a low potential have low start-up rates. Furthermore, the results show secondly that the combination of factor endowments seems to be important as well. Completely different regional combinations of factors conducive for entrepreneurial activity can lead to similar high or low start-up rates. Hence, not only single factors shape firm formation rates in regions. It is also the combination and interrelationship of the various parameters which can be important for different types of regions. The findings of this study may have implications for policy makers in that they have not only the opportunity to influence single factors in order to increase the dynamics of entrepreneurial activity in their region. They need to focus on the region specific structure. It also means that other regions cannot easily be used as a benchmark. For regional policy, each region has to incorporate its own specific combination of factors conducive for new venture creation.
Keywords: R11; L26; R58; 330; Regional Economics; Entrepreneurship; Business Formation